Defining a Patient-Centred Core Outcome Domain Set for the Assessment of Hearing Rehabilitation With Clients and Professionals - Allen, David; Hickson, Louise; Ferguson, Melanie (Frontiers in Neuroscience, 2022)
Background: A variety of outcome domains are currently measured for the assessment of hearing rehabilitation. There is no consensus about which outcome domains should be measured, when, and how. In addition, most studies seeking to develop outcome sets and measures for hearing rehabilitation have focused on researchers and clinicians, rather than also involving clients. Experience-based co-design suggests health services professionals should work with clients to design services and metrics. Objectives: This study aimed to seek consensus from stakeholders to define which patient-centred outcome domains should be measured, when, and how, in a national publicly-funded hearing rehabilitation scheme. In addition, the study aimed to identify potential mechanisms to standardise collection and reporting of data. Methods: Two groups participated in a three-round online Delphi process: 1) 79 professionals involved in the delivery of hearing services in Australia, and 2) 64 hearing services consumers. An initial set of in-person workshops scoped key issues upon which to develop two rounds of online surveys. The most important outcome domains were presented to a consensus workshop of 7 professionals and 3 client advocates, who agreed on four domains. Results: A range of domains were identified as relevant indicators of hearing rehabilitation, with the top four being communication ability, wellbeing, personal relationships, and participation restrictions. There was little agreement on timepoints for collection, except that this should be established by research once outcome measures have been selected. There was agreement that outcomes should be collected before hearing rehabilitation and no earlier than 3 months following rehabilitation completion. Potential benefits and issues with the development of a national outcomes database were identified, with participants highlighting the importance of valid, high-quality, trustworthy, and comprehensive data collection. Conclusion: These results suggest a set of outcome domains for the evaluation of hearing rehabilitation, and provide important background information for their implementation into hearing healthcare systems. The range of suggested outcome domains, potential purposes for outcomes collection, and potential concerns with the establishment of centralised national outcomes systems suggest that ongoing stakeholder engagement will be vital. In addition, significant further research is required to determine the optimal time of outcomes collection.